CONSTRUCTION SOLUTION OF FOLDED-PLATE SHELL FOUNDATION FOR POWER TRANSMISSION TOWERS - Timchenko, R. A.; Krishko, D. A.; Khoruzhenko, I. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article presents the practice of applying different types of shell foundations. The peculiarities of foundation design for power transmission towers under complex engineering and geological conditions are considered. It is defined that under uneven deformations of the base when applying folded-plate shell foundations on weak or water-saturated soils load from the foundation must be uniformly redistributed to the ground base. It is proposed to use an alternative construction solution of the folded-plate foundation for power transmission towers with a hinged system for fastening folds comprising supporting beams. The improved design of the folded-plate shell foundation for power transmission towers can be used on water-saturated, marshy, weak soils and under uneven deformations of the base.
Keywords: shell foundation; hinge system; power transmission towers; , folded-plate foundation